A Comparison of Forecasting Method of Number of Customer Accounts that use the Service Internet Banking using Box-Jenkins Method and Holt’s method - Kanya Bowornchockchai (Warasan Witthayasat Lae Theknoloyi Mahawitthayalai Mahasarakham, 2019)
The purpose of this research was to study and compare the forecasting methods for number of customer accounts that use the service internet banking by using Box-Jenkins method and Holt’s method. Time series data were divided into two groups, the first group was monthly from March 2010 to April 2017 of 86 value for identification models. The second group was monthly from May 2017 to April 2018 of 12 value for checking the accuracy of the forecasting models via the criterion of the lowest mean absolute percentage error (MAPE). The lowest MAPE was used as the criteria of each period. Results show that Box-Jenkins method gives mean absolute percent error (MAPE) lower than Holt’s method. The suitable forecasting model is ARIMA (0,1,1) and the forecasting equation is t t t t-1 lnZ = 0.0197 + lnZ + a + 0.4034a